Metabolic syndrome triggered by fructose diet impairs neuronal function and vascular integrity in ApoE-KO Mouse Retinas: Implications of autophagy deficient activation - Paz, Maria Constanza (2020)
Metabolic syndrome is a disorder characterized by a constellation of clinical findings such as elevated blood glucose, hyperinsulinemia, dyslipidemia, hypertension, and obesity. A positive correlation has been found between metabolic syndrome or its components and retinopathy, mainly at microvascular level, in patients without a history of diabetes. Here, we extend the investigations beyond the vascular component analyzing functional changes as well as neuronal and glial response in retinas of Apolipoprotein E knockout (ApoE-KO) mice fed with 10% w/v fructose diet. Given that autophagy dysfunction is implicated in retinal diseases related to hyperglycemia and dyslipidemia, the activation of this pathway was also analyzed. Two months of fructose intake triggered metabolic derangements in ApoE-KO mice characterized by dyslipidemia, hyperglycemia and hyperinsulinemia. An increased number of TUNEL positive cells, in addition to the ganglion cell layer, was observed in the inner nuclear layer in retina. Vascular permeability, evidenced by albumin?Evans blue leakage and extravasation of albumin was also detected. Furthermore, a significant decrease of the glial fibrillary acidic protein expression was confirmed by Western blot analysis. Absence of both Müller cell gliosis and pro-angiogenic response was also demonstrated. Finally, retinas of ApoE-KO FD mice showed defective autophagy activation as judged by LC3B mRNA and p62 protein levels correlating with the increased cell death. These results demonstrated that FD induced in ApoE-KO mice biochemical alterations compatible with metabolic syndrome associated with neuronal impairment and mild vascular alterations in the retina.